Immunoenhancing effects of Gynostemma Pentaphyllum Extract on mucosal immunity against porcine epidemic diarrhea virus - Yanxiang Zhang; Ruihan Tang; Ruihan Tang; Yuanqing Liu; Zhihui Hao; Zhihui Hao; Zhihui Hao; Kai Fan; Shanshan Xie; Bo Tang; Shuaiyu Wang; Shuaiyu Wang; et al. (Frontiers in Veterinary Science)
IntroductionThis study investigated the mucosal immunoadjuvant effects of Gynostemma Pentaphyllum Extract (Gynostemma P.E), the bioactive constituents of Gynostemma pentaphyllum, against porcine epidemic diarrhea virus (PEDV).MethodsTwenty-four mice were randomly divided into four groups: a negative control group (intranasal administration of antigen only), a Gynostemma P.E-antigen mixture test group (intranasal administration), and two positive control groups (intramuscular injection of antigen or inactivated homemade vaccine, respectively). Fourteen days post booster immunization, spleen samples were collected to assess splenic lymphocyte proliferation activity. Intestinal segments were harvested for histological evaluation; duodenal intraepithelial lymphocytes (IELs) and IgA-positive cell numbers were quantified via H&E staining and immunohistochemistry (IHC). Serum and mucosal lavage fluid were analyzed for specific IgG and secretory IgA (sIgA) antibody levels.ResultsThe results demonstrated that Gynostemma P.E significantly promoted immune organ development, enhanced splenic lymphocyte proliferation (p < 0.05), and elevated serum IgG and nasal mucosal sIgA antibody levels (p < 0.05).DiscussionThis study presents an innovative approach that integrates bioactive compounds from traditional Chinese medicine with intranasal mucosal immunization, offering new perspectives for combating gastrointestinal infections in veterinary medicine, and demonstrates that Gynostemma P.E significantly enhance PEDV-specific mucosal immunity in mice, providing a foundation for developing safer and more effective PEDV vaccines (and other veterinary vaccines), data supporting Gynostemma P.E as mucosal immunoadjuvants, and a theoretical framework for future clinical trials.